Functional ionic liquid additive, electrolyte and high-voltage lithium ion battery

Through the functional ionic liquid additive with a large ion radius in lithium-ion batteries, the problem of high viscosity and poor stability of the electrolyte at high pressure is solved, and a high-stability SEI film is formed, which improves the high-temperature cycling performance of the battery.

CN119208730AActive Publication Date: 2024-12-27LIONGO (CHANGZHOU) NEW ENERGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411300422.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-14
Publication Date
2024-12-27
Estimated Expiration
2044-09-14

AI Technical Summary

Technical Problem

The existing ionic liquid electrolyte has problems such as high viscosity, poor anion thermal stability and high pressure stability under high pressure, which leads to unstable SEI film and affects the circulation performance of lithium-ion batteries.

Method used

A functional ion liquid additive was developed, which consists of cations and anions with large ion radius, which is easy to dissociate, increases the solvation of anions on the positive electrode, forms a high-stability SEI film, and relieves the interface through the functional functional groups of the cations. Destruction and improve battery high-temperature cycling performance.

Benefits of technology

The low viscosity and low decomposition electrolyte are achieved, forming a thin and strong SEI film, improving the cycling performance of lithium-ion batteries at high voltage and high temperatures, and extending battery life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005048233150000021
    Figure BDA0005048233150000021
  • Figure BDA0005048233150000031
    Figure BDA0005048233150000031
  • Figure BDA0005048233150000032
    Figure BDA0005048233150000032
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a functional ionic liquid additive, an electrolyte and a high-voltage lithium ion battery. The structure of the functional ionic liquid additive is composed of positive ions and negative ions, the positive ions and the negative ions have large ionic radiuses and are easy to dissociate, and Li < + > with smaller radiuses is easier to combine with the negative ions, so that the solvation structure of the electrolyte is changed, more functional negative ions participate in a solvation sheath layer, and the stability of the electrolyte is improved. According to the present invention, more anions can participate in the solvation configuration coordination under the conventional concentration so as to finally induce the formation of the anion-derived SEI film, and the anion-derived SEI film contains more high Young modulus LiF, such that the anion-derived SEI film is thin and firm, and is not easily broken during the circulation process, and the functional group contained in the cation group can alleviate the damage of the free acid in the electrolyte on the positive and negative electrode interface film so as to provide the positive and negative electrode interface film with the good stability; the interface stability is further improved, so that the high-temperature cycle performance of the battery is intuitively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a functional ionic liquid additive, an electrolyte and a high-voltage lithium-ion battery. Background Art

[0002] With the increase of battery energy density, the voltage of positive electrode materials continues to increase, which drives the electrochemical window of electrolytes to expand continuously, resulting in the electrochemical window of traditional electrolytes can no longer meet the needs of high-voltage materials. For example, the voltage platform of lithium nickel manganese oxide is 4.7V, and the traditional electrolyte begins to oxidatively decompose at 4.3V, which deteriorates the positive electrode interface and cannot give full play to the advantages of high-voltage materials. In addition, traditional electrolytes also have a series of problems such as volatility, flammability and environmental impact. In order to overcome these problems, ionic liquids have been introduced as an alternative electrolyte or additive. Because of their low volatility, high chemical stability and wide electrochemical window, they have attracted much attention in the field of high-voltage electrolytes. At the same time, how to form a stable SEI film is crucial. An unstable SEI film will break during battery cycling and consume a large amount of active lithium. At the same time, the accumulation of SEI film will increase the transport energy barrier of ions, resulting in slow interface dynamics. Therefore, it is very necessary to finely control the interfacial reaction and generate a uniform, stable and strong SEI film. In recent years, anion-derived SEI has shown great advantages in improving the electrochemical performance of batteries due to its high mechanical strength, high ionic conductivity, and fast ion diffusion.

[0003] At present, the commonly used cations in electrolytes include imidazolium cations, piperidinium cations, pyrrole cations, quaternary ammonium cations, etc., and the anions include PF 6- , BF 4- , bis(fluorosulfonyl)imide anion (FSI - ), bis(trifluoromethanesulfonyl imide) anion (TFSI - ) etc. However, there are still some challenges in existing ionic liquid electrolytes, including high viscosity and unsatisfactory thermal stability and high-voltage stability of anions. Although most ionic liquid anions can form a stable SEI film on the surface of the negative electrode, the protection of the positive electrode is weaker than that of the negative electrode. In addition, the solvation ability of the anion is the key to the formation of anion-derived SEI film, which is highly dependent on the competitive coordination between solvent-cation and anion-cation. By introducing weakly solvating solvents or anions with strong coordination ability, more anions can be involved in the solvation configuration coordination at conventional concentrations, thereby changing the solvation structure of the electrolyte.

[0004] Therefore, it is necessary to develop a new type of ionic liquid with low viscosity, high oxidation potential, and not easy to decompose under high pressure. The anion can form an effective passivation film at the positive electrode, effectively reducing the phase change of the positive electrode material and interfacial side reactions under high pressure, thereby meeting the long cycle requirements of high-voltage system batteries. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a functional ionic liquid additive, an electrolyte and a high-voltage lithium-ion battery; the structure of the functional ionic liquid additive is composed of cations and anions, and both the anions and cations have a large ionic radius and are easy to dissociate, and the Li + It is easier to combine with anions, thus changing the solvation structure of the electrolyte. More functional anions participate in the solvation sheath, which can achieve more anions participating in the solvation configuration coordination at conventional concentrations, thereby ultimately inducing the formation of anion-derived SEI film, which contains more LiF with high Young's modulus, so it is thin and strong, and not easy to break during the cycle. At the same time, the functional functional groups contained in the cationic groups can alleviate the damage of the free acid in the electrolyte to the positive and negative electrode interface films, further improving the interface stability, thereby intuitively improving the high-temperature cycle performance of the battery.

[0006] The present invention provides a functional ionic liquid additive having a structure shown in formula B:

[0007]

[0008] Wherein, m and n are each independently an integer of 1 to 5;

[0009] R1 is selected from hydrogen, C1-C5 alkyl, C2-C5 alkenyl or C2-C5 alkynyl;

[0010] R2 to R5 are each independently selected from hydrogen, a C1 to C5 alkyl group, a C2 to C5 alkenyl group, a C2 to C5 alkynyl group, a halogen atom or a C1 to C5 nitrile group;

[0011] R6 is selected from C1-C5 alkyl groups.

[0012] Preferably, it has a structure shown in structural formula A:

[0013]

[0014] wherein R1 is selected from hydrogen, C1-C5 alkyl, C2-C5 alkenyl or C2-C5 alkynyl;

[0015] R2 to R5 are each independently selected from hydrogen, a C1 to C5 alkyl group, a C2 to C5 alkenyl group, a C2 to C5 alkynyl group, a halogen atom or a C1 to C5 nitrile group.

[0016] Preferably, R1 is selected from hydrogen, methyl, ethyl, vinyl, ethynyl or propynyl;

[0017] R2 to R5 are each independently selected from hydrogen, vinyl, acetylene, fluorine or acetonitrile.

[0018] Preferably, the functional ionic liquid additive has at least one of the structures shown in formula (I) to formula (VI):

[0019]

[0020] The present invention also provides a method for preparing a functional ionic liquid additive, comprising the following steps:

[0021] The lithium borate salt represented by formula (VII) is reacted with the compound represented by formula (VIII) to obtain a functional ionic liquid additive having a structure represented by formula B;

[0022]

[0023] Wherein, m and n are each independently an integer of 1 to 5;

[0024] R1 is selected from hydrogen, C1-C5 alkyl, C2-C5 alkenyl or C2-C5 alkynyl;

[0025] R2 to R5 are each independently selected from hydrogen, a C1 to C5 alkyl group, a C2 to C5 alkenyl group, a C2 to C5 alkynyl group, a halogen atom or a C1 to C5 nitrile group;

[0026] R6 is selected from C1-C5 alkyl groups.

[0027] The present invention also provides a non-aqueous electrolyte comprising the above-mentioned functional ionic liquid additive.

[0028] Preferably, the mass of the functional ionic liquid additive is 0.5% to 3% of the mass of the non-aqueous electrolyte.

[0029] Preferably, the non-aqueous electrolyte further comprises a lithium salt, a non-aqueous solvent and an auxiliary electrolyte additive;

[0030] The mass of the lithium salt is 14% to 16% of the mass of the non-aqueous electrolyte;

[0031] The mass of the non-aqueous solvent is 79% to 81.5% of the mass of the non-aqueous electrolyte;

[0032] The mass of the auxiliary electrolyte additive is 2% to 3.8% of the mass of the non-aqueous electrolyte.

[0033] Preferably, the lithium salt is selected from one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium difluorobis(oxalatophosphate);

[0034] The non-aqueous solvent is selected from organic esters and / or ether solvents; the organic ester is selected from one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, ethyl formate, ethyl acetate, propyl acetate, propyl propionate, methyl trifluoroethyl carbonate, fluoroethylene carbonate and di(2,2,2-trifluoroethyl) carbonate; the ether solvent is selected from one or more of dimethyl ether, diethyl ether, methyl ethyl ether, ethylene glycol dimethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether;

[0035] The auxiliary electrolyte additive is selected from one or more of unsaturated cyclic carbonate compounds, fluorinated carbonate compounds, sulfate compounds, sulfonate compounds, sulfonimide compounds, phosphate compounds, silane compounds, trimethylsilyl ester compounds, isocyanate compounds, nitrile compounds and lithium salt additives.

[0036] The present invention also provides a high-voltage lithium-ion battery, comprising the above-mentioned non-aqueous electrolyte.

[0037] Compared with the prior art, the present invention has the following beneficial effects:

[0038] (1) The novel functional ionic liquid compound proposed in the present invention is used as an electrolyte additive in lithium-ion batteries and has the advantages of low vapor pressure and wide electrochemical window of ionic liquids. Compared with traditional pyrrole ionic liquids, the molecular structure of anions and cations of the ionic liquid is relatively small, the intermolecular force is weak, and the viscosity is low. In addition, trimethylsilane is introduced into the pyrrole cation to increase the polarity of the ionic liquid, reduce the intermolecular force, and further reduce the viscosity of the ionic liquid.

[0039] (2) The novel functional ionic liquid compound proposed by the present invention has a structure in which the anions and cations contained have large ionic radii, so the complexing ability is weak and easy to dissociate. The smaller radius of Li+ is easier to combine with anions, thus changing the solvation structure of the electrolyte. More functional anions participate in the solvation sheath, which can achieve more anions participating in the solvation configuration coordination at conventional concentrations, thereby forming an anion-derived high-stability SEI film. At the same time, the special functional groups contained in the anion and cation structures can also play a role in removing free acids in the electrolyte, complexing and stabilizing high-valent transition metals, etc., thereby further improving the electrochemical performance of high-voltage lithium-ion batteries. DETAILED DESCRIPTION

[0040] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0041] The present invention provides a functional ionic liquid additive, characterized in that it has a structure shown in formula B:

[0042]

[0043] Here, m and n are each independently an integer of 1 to 5, preferably an integer of 1 to 4, more preferably an integer of 1 to 3, and most preferably 1 or 2.

[0044] R1 is hydrogen, C1-C5 alkyl, C2-C5 alkenyl or C2-C5 alkynyl, preferably hydrogen, C1-C3 alkyl, C2-C3 alkenyl or C2-C3 alkynyl, more preferably hydrogen, methyl, ethyl, vinyl, ethynyl or propynyl.

[0045] R2~R5 are each independently hydrogen, C1~C5 alkyl, C2~C5 alkenyl, C2~C5 alkynyl, halogen atom or C1~C5 nitrile group, preferably hydrogen, C1~C4 alkyl, C2~C4 alkenyl, C2~C4 alkynyl, halogen atom or C1~C4 nitrile group, more preferably hydrogen, C1~C3 alkyl, C2~C3 alkenyl, C2~C3 alkynyl, halogen atom or C1~C3 nitrile group, further preferably hydrogen, vinyl, ethynyl, fluorine atom or acetonitrile group.

[0046] Further preferably, at least one of R1, R2 to R5 is an unsaturated group or a halogen atom; the halogen atom may be any halogen atom well known to those skilled in the art without any particular limitation, and may specifically be fluorine, chlorine or bromine, more preferably a fluorine atom.

[0047] R6 is a C1-C5 alkyl group, preferably a C1-C4 alkyl group, more preferably a C1-C3 alkyl group, and still more preferably a methyl group or an ethyl group.

[0048] In a specific embodiment provided by the present invention, the functional ionic liquid additive has a structure shown in structural formula A:

[0049]

[0050] Here, m and n are each independently an integer of 1 to 5, preferably an integer of 1 to 4, more preferably an integer of 1 to 3, and most preferably 1 or 2.

[0051] R1 is hydrogen, C1-C5 alkyl, C2-C5 alkenyl or C2-C5 alkynyl, preferably hydrogen, C1-C3 alkyl, C2-C3 alkenyl or C2-C3 alkynyl, more preferably hydrogen, methyl, ethyl, vinyl, ethynyl or propynyl.

[0052] R2~R5 are each independently hydrogen, C1~C5 alkyl, C2~C5 alkenyl, C2~C5 alkynyl, halogen atom or C1~C5 nitrile group, preferably hydrogen, C1~C4 alkyl, C2~C4 alkenyl, C2~C4 alkynyl, halogen atom or C1~C4 nitrile group, more preferably hydrogen, C1~C3 alkyl, C2~C3 alkenyl, C2~C3 alkynyl, halogen atom or C1~C3 nitrile group, further preferably hydrogen, vinyl, ethynyl, fluorine atom or acetonitrile group.

[0053] Further preferably, at least one of R1, R2 to R5 is an unsaturated group or a halogen atom; the halogen atom may be any halogen atom well known to those skilled in the art without any particular limitation, and may specifically be fluorine, chlorine or bromine, more preferably a fluorine atom.

[0054] R6 is a C1-C5 alkyl group, preferably a C1-C4 alkyl group, more preferably a C1-C3 alkyl group, and still more preferably a methyl group or an ethyl group.

[0055] In another specific embodiment provided by the present invention, the functional ionic liquid additive has at least one of the structures shown in formula (I) to formula (VI):

[0056]

[0057] The structure of the functional ionic liquid additive provided by the present invention is composed of cations and anions. Both cations and anions have large ionic radii, so the complexing ability is weak and it is easy to dissociate. + It is easier to combine with anions, thus changing the solvation structure of the electrolyte, and more functional anions participate in the solvation sheath, which can achieve more anions participating in the solvation configuration coordination at conventional concentrations, thereby forming an anion-derived high-stability SEI film. At the same time, the special functional groups contained in the anion and cation structures can also play a role in removing free acids in the electrolyte, complexing and stabilizing high-valent transition metals, etc., thereby further improving the electrochemical performance of high-voltage lithium-ion batteries.

[0058] The present invention also provides a method for preparing a functional ionic liquid additive, comprising the following steps: reacting a lithium borate salt represented by formula (VII) with a compound represented by formula (VIII) to obtain a functional ionic liquid additive having a structure represented by formula B;

[0059]

[0060]

[0061] wherein m and n are each independently an integer of 1 to 5; R1 is hydrogen, a C1 to C5 alkyl group, a C2 to C5 alkenyl group or a C2 to C5 alkynyl group; R2 to R5 are each independently hydrogen, a C1 to C5 alkyl group, a C2 to C5 alkenyl group, a C2 to C5 alkynyl group, a halogen atom or a C1 to C5 nitrile group; and R6 is a C1 to C5 alkyl group.

[0062] The present invention has no special restrictions on the sources of all raw materials, which can be commercially available or homemade; the m, n, R1, R2-R5 and R6 are the same as those described above and will not be repeated here.

[0063] According to the present invention, the lithium borate salt represented by formula (VII) is preferably prepared according to the following method: reacting the compound represented by formula (IX) with lithium tetrafluoroborate to obtain the lithium borate salt represented by formula (VII); the molar ratio of the compound represented by formula (IX) to lithium tetrafluoroborate is preferably 2 to 2.5:1, more preferably 2.2:1; the reaction temperature is preferably 50°C to 70°C, more preferably 55°C to 65°C, and more preferably 60°C; the reaction time is preferably 6 to 8h.

[0064]

[0065] In a specific embodiment provided by the present invention, the compound represented by formula (IX) is preferably reacted with lithium tetrafluoroborate in a protective atmosphere; the protective atmosphere is preferably nitrogen.

[0066] In a specific embodiment provided by the present invention, the compound represented by formula (IX) reacts with lithium tetrafluoroborate in the presence of silicon tetrachloride; the molar ratio of the compound represented by formula (IX) to silicon tetrachloride is preferably 1:0.5-0.8, more preferably 1:0.6-0.7; the reaction is preferably carried out in an organic solvent; the organic solvent is an organic solvent well known to those skilled in the art, without any special restrictions, and is preferably ultra-dry dichloromethane in the present invention.

[0067] In a specific embodiment provided by the present invention, lithium tetrafluoroborate, silicon tetrachloride and an organic solvent are preferably mixed and heated first, and then an organic solution containing the compound represented by formula (IX) is added dropwise. After the addition is completed, the heating reaction is continued to obtain a lithium borate salt represented by formula (VII); the temperature of the mixed heating is preferably 50°C to 70°C, more preferably 55°C to 65°C, and more preferably 60°C; the concentration of the compound represented by formula (IX) in the organic solution containing the compound represented by formula (IX) is preferably 3 to 5 mol / L, more preferably 4 to 5 mol / L, and more preferably 4.4 to 4.5 mol / L; the organic solution containing the compound represented by formula (IX) is preferably controlled to be added dropwise within 1 hour; the temperature of the heating reaction is preferably 50°C to 70°C, more preferably 55°C to 65°C, and more preferably 60°C; the heating reaction time is preferably 6 to 8 hours, and more preferably 7 hours.

[0068] After the reaction is completed, it is preferably cooled to room temperature, a saturated sodium bicarbonate solution and water are added, and then extracted with an organic solvent, the organic layer is collected, washed with saturated brine and dried with a desiccant, and then concentrated under reduced pressure. The residue is washed with a mixed solution of dichloromethane and petroleum ether, and dried to obtain a lithium borate salt represented by formula (VII); the organic solvent is preferably dichloromethane; the volume ratio of dichloromethane to petroleum ether in the mixed solution of dichloromethane and petroleum ether is preferably (1-2): (9-8), more preferably 1:9.

[0069] According to the present invention, the compound represented by formula (VIII) is preferably prepared according to the following method: reacting the compound represented by formula (X) with the compound represented by formula (XI) to obtain the compound represented by formula (VIII); the molar ratio of the compound represented by formula (X) to the compound represented by formula (XI) is preferably 1:(1-1.3), more preferably 1:1.1; the reaction temperature is preferably 70°C-90°C, more preferably 75°C-85°C, and even more preferably 80°C; the reaction time is preferably 20-30h, more preferably 24h.

[0070]

[0071] In a specific embodiment provided by the present invention, the compound represented by formula (X) and the compound represented by formula (XI) are preferably reacted in a protective atmosphere; the protective atmosphere is preferably nitrogen.

[0072] In a specific embodiment provided by the present invention, the compound represented by formula (X) and the compound represented by formula (XI) are preferably reacted in an organic solvent; the organic solvent is an organic solvent well known to those skilled in the art without any special limitation, and N,N-dimethylformamide (DMF) is preferred in the present invention.

[0073] After the reaction is completed, the solvent is preferably removed, and the residue is washed with anhydrous ether and dried to obtain a compound represented by formula (VIII).

[0074] The lithium borate salt represented by formula (VII) is reacted with the compound represented by formula (VIII); the molar ratio of the lithium borate salt represented by formula (VII) to the compound represented by formula (VIII) is preferably 1:1; the reaction is preferably carried out in water, more preferably in deionized water; the reaction is preferably carried out under stirring; the reaction time is preferably 2 to 4 hours, more preferably 2.5 to 3.5 hours, and more preferably 3 hours.

[0075] After the reaction is completed, the solvent is preferably removed, washed with dichloromethane, and concentrated and dried to obtain a functional ionic liquid additive having a structure shown in formula B; the method for removing the solvent is a method well known to those skilled in the art and is not particularly limited. In the present invention, it is preferably concentrated under reduced pressure; the number of times of washing with dichloromethane is preferably 2 to 4 times, more preferably 3 times.

[0076] In a specific embodiment provided by the present invention, the functional ionic liquid additive is synthesized according to the following route:

[0077]

[0078] The present invention also provides a non-aqueous electrolyte comprising the above-mentioned functional ionic liquid additive.

[0079] According to the present invention, the mass of the ionic liquid additive is preferably 0.1% to 0.3% of the mass of the non-aqueous electrolyte, more preferably 0.5% to 3%, further preferably 1% to 3%, further preferably 1.5% to 2.5%, and most preferably 2%.

[0080] According to the present invention, the non-aqueous electrolyte preferably also includes a lithium salt; the lithium salt can be a lithium salt well known to those skilled in the art without any special restrictions. In the present invention, it is preferably one or more of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium bistrifluoromethylsulfonyl imide (LiTFSI), lithium bisfluorosulfonyl imide (LiFSI), lithium bisoxalatoborate (LiBOB), lithium difluorooxalatoborate (LiODFB) and lithium difluorobisoxalatophosphate (LiDODFP); the mass of the lithium salt is preferably 14% to 16% of the mass of the non-aqueous electrolyte.

[0081] According to the present invention, the non-aqueous electrolyte preferably further comprises a non-aqueous solvent; the non-aqueous solvent is a non-aqueous solvent well known to those skilled in the art, and is not particularly limited. In the present invention, it is preferably an organic ester and / or ether solvent; the organic ester is preferably ethylene carbonate, propylene carbonate (PC), butylene carbonate, dimethyl carbonate (DMC), diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, ethyl propyl carbonate, ethyl formate, ethyl acetate, propyl acetate, propyl propionate, methyl trifluoroethyl carbonate (FEMC), fluoroethylene carbonate (FEC) and one or more of di(2,2,2-trifluoroethyl) carbonate (TFEC); the ether solvent is preferably dimethyl ether, diethyl ether, methyl ethyl ether, ethylene glycol dimethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 1H,1H,5H- One or more of octafluoropentyl-1,1,2,2-tetrafluoroethyl ether; in the embodiments provided by the present invention, propylene carbonate (PC), fluoroethylene carbonate (FEC), methyl trifluoroethyl carbonate (FEMC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are specifically used as non-aqueous solvents for illustration; the mass ratio of propylene carbonate (PC), fluoroethylene carbonate (FEC), methyl trifluoroethyl carbonate (FEMC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) is preferably 5: (5-15): (5-15): (30-50): (30-40), more preferably 5: (5-15): (5-15): (35-45): (30-40), and more preferably 5: 10: 10: 40: 35; the mass of the non-aqueous solvent is preferably 79% to 81.5% of the mass of the non-aqueous electrolyte.

[0082] According to the present invention, the non-aqueous electrolyte preferably further comprises an auxiliary electrolyte additive; the auxiliary electrolyte additive is preferably one or more of unsaturated cyclic carbonate compounds, fluorocarbonate compounds, sulfate compounds, sulfonate compounds, sulfonimide compounds, phosphate compounds, silane compounds, trimethylsilyl ester compounds, isocyanate compounds, lithium salt additives and nitrile compounds; the unsaturated cyclic carbonate compound is preferably vinylene carbonate (VC) and / or vinyl ethylene carbonate (VEC); The fluorocarbonate compound is preferably fluoroethylene carbonate (FEC); the sulfate compound is preferably one or more of vinyl sulfate, vinyl bissulfate, propylene sulfate and propylene bissulfate; the sulfonate compound is preferably one or more of 1,3-propane sultone, 1,3-propylene sultone, 1,4-butane sultone, 2,4-butane sultone, phenyl methanesulfonate and methylene disulfonate; the sulfonimide compound is preferably N-phenylbis(trifluoromethanesulfonyl)imide; the phosphate compound is preferably trifluoromethanesulfonyl imide. One or more of allyl phosphate, tris(trimethylsilyl)phosphate, trimethyl phosphite, triphenyl phosphite, tetramethylmethylene diphosphate and propargyl phosphate; the silane compound is preferably (2-allylphenoxy)trimethylsilane; the trimethylsilyl ester compound is preferably tris(trimethylsilyl)borate; the isocyanate compound is preferably one or more of 1,3,5-triallyl isocyanurate, isocyanoethyl methacrylate, hexamethylene diisocyanate, p-phenylene diisocyanate and 2,4-toluene diisocyanate; The lithium salt additive can be any lithium salt additive well known to those skilled in the art without any special limitation. In the present invention, it is preferably one or more of lithium difluorobis(oxalate)phosphate (LiDODFP), lithium tetrafluorophosphate oxalate, lithium tetrafluorooxalatoborate phosphate and lithium difluorophosphate; the nitrile compound is preferably one or more of adiponitrile, succinonitrile, glutaronitrile, 1,3,6-hexanetrinitrile and 1,2-bis(cyanoethoxy)ethane; the mass of the auxiliary electrolyte additive is preferably 2% to 5% of the mass of the non-aqueous electrolyte, more preferably 2% to 3.8%.

[0083] The present invention also provides a high-voltage lithium-ion battery and the above-mentioned non-aqueous electrolyte.

[0084] Specifically, the high-voltage lithium-ion battery includes a positive electrode, a separator, a negative electrode and the above-mentioned non-aqueous electrolyte.

[0085] More specifically, the positive electrode includes a positive electrode active material; the positive electrode active material is preferably one or more of lithium cobalt oxide, lithium manganese oxide, ternary nickel cobalt manganese lithium, lithium nickel manganese oxide, lithium iron phosphate and lithium manganese iron phosphate, more preferably lithium nickel manganese oxide.

[0086] More specifically, the negative electrode includes a negative electrode active material; the negative electrode active material is preferably one or more of artificial graphite, natural graphite, lithium titanate, metallic lithium, silicon-carbon composite material and silicon monoxide, more preferably artificial graphite.

[0087] More specifically, the diaphragm is preferably polypropylene, polyethylene diaphragm, polyethylene diaphragm coated with aluminum oxide on one side, and more preferably polyethylene diaphragm coated with aluminum oxide on one side.

[0088] The lithium ion battery made of the non-aqueous electrolyte of the present invention has better electrochemical performance, which is specifically manifested in that the room temperature and high temperature electrochemical performance of the prepared lithium nickel manganese oxide lithium ion battery in the voltage range of 3.0 to 4.8V is greatly improved.

[0089] In order to further illustrate the present invention, a functional ionic liquid additive, an electrolyte and a high-voltage lithium-ion battery provided by the present invention are described in detail below in conjunction with embodiments.

[0090] The reagents used in the following examples are all commercially available.

[0091] Example 1

[0092] The specific steps for preparing compound (I) are as follows:

[0093]

[0094] Under nitrogen atmosphere, add 200 mL of ultra-dry dichloromethane to a clean and dry 500 mL three-necked flask equipped with a magnetic rotor, then add lithium tetrafluoroborate (9.40 g, 100.00 mmol) and silicon tetrachloride (11.20 g, 66.67 mmol), then start stirring and heating, and after the system temperature reaches the set 60°C, slowly add 50 mL of ultra-dry dichloromethane solution containing 3-hydroxypropionitrile (15.63 g, 220.00 mmol) to the reaction system through a constant pressure dropping funnel, and control the dripping within 1 hour. Then continue to heat and stir the reaction system for 7 hours. After the reaction was completed, the mixture was cooled to room temperature, saturated sodium bicarbonate solution (150 mL) was added to the reaction mixture, and then 100 mL of deionized water was added, and then the mixed solution was extracted three times with 100 mL of dichloromethane, and the organic layer was collected and combined, washed with saturated saline solution and dried over anhydrous sodium sulfate, and concentrated under reduced pressure. The residue was washed three times with 50 mL of dichloromethane / petroleum ether mixed solution (volume ratio 10:90), and dried to obtain the desired product, difluorodicyanoethoxyborate lithium salt, with a yield of 82.2%. HRMS (m / z): calcd. for C6H8O2N2F2B - :189.07,found189.18.

[0095]

[0096] Under nitrogen atmosphere, 100 mL of ultra-dry N,N-dimethylformamide (DMF) was added to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, followed by N-vinylpyrrolidine (9.71 g, 100.00 mmol) and chloromethyltrimethylsilane (13.42 g, 110 mmol), followed by stirring and heating, and the mixture was reacted at 80°C for 24 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and then washed with 100 mL of anhydrous ether, and the solvent was removed by concentration under reduced pressure to obtain intermediate 1 with a yield of 82.5%. Subsequently, intermediate 1 (10.96 g, 50.00 mmol), lithium difluorodicyanoethoxyborate (9.80 g, 50.00 mmol) and 100 mL of deionized water were added to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, and the reaction was stopped after stirring for 3 h. After the solvent was removed by distillation under reduced pressure, the product was washed three times with 50 mL of dichloromethane and finally concentrated and dried to obtain the target ionic liquid compound (I) with a yield of 76.4%. HRMS (m / z): calcd.for C 16 H 30 O2N3F2BSi:373.22, found 373.31.

[0097] Prepare the electrolyte 1 sample, the specific steps are as follows:

[0098] In an argon glove box with a water and oxygen content of ≤0.1ppm, propylene carbonate (PC), fluoroethylene carbonate (FEC), methyl trifluoroethyl carbonate (FEMC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) are uniformly mixed in a mass ratio of 5:10:10:40:35 to obtain an organic solvent, and then lithium salt LiPF6 and lithium difluorobis(oxalate) phosphate (LiDODFP) are slowly added to the organic solvent, and after complete dissolution, 1,3-propane sultone (PS), vinyl sulfate (DTD) and ionic liquid compound (I) are added, and the electrolyte 1 is obtained after uniform stirring, wherein the usage amounts of LiPF6, LiDODFP, organic solvent, PS, DTD and ionic liquid compound (I) are 10%, 5%, 80%, 2%, 1% and 2% of the total mass of the electrolyte, respectively.

[0099] Prepare the experimental battery 1 sample, the specific steps are as follows:

[0100] Preparation of positive electrode sheet: The positive electrode material lithium nickel manganese oxide LiNi 0.5 Mn 1.5O4 (LNMO), conductive agent carbon black (SuperP), carbon nanotubes (CNT, NMP solution with a content of 5% by mass) and binder polyvinylidene fluoride (PVDF, NMP solution with a content of 5% by mass) were weighed and mixed in a mass ratio of 97:0.7:0.8:1.5. After mixing, an appropriate amount of NMP was added to control the theoretical solid content to 65%. A planetary homogenizer was used to homogenize the positive electrode slurry, and the positive electrode slurry was evenly coated on an aluminum foil with a thickness of 12 μm. The double-sided coating surface density was 350 g / m 2 , compacted density is 3.0g / cm 3 After drying, rolling and cutting, a 50mm×70mm positive electrode sheet is obtained.

[0101] Preparation of diaphragm: A polyethylene diaphragm coated with aluminum oxide on one side was used as the isolation membrane and was placed in a dry room with a dew point of -35°C for 72 hours before use.

[0102] Preparation of negative electrode sheet: artificial graphite (capacity 355 mAh g -1 ), conductive agent SuperP, thickener sodium carboxymethyl cellulose (CMC, deionized water solution with a solid content of 1.5%), and binder styrene butadiene rubber (SBR, deionized water solution with a solid content of 48%) were mixed in a mass ratio of 95:1:1.5:2.5, and deionized water was added after the mixing was completed. The theoretical solid content was controlled to be 52%, and the negative electrode slurry was obtained by homogenization using a planetary homogenizer, and the negative electrode slurry was evenly coated on a copper foil with a thickness of 6 μm. After drying, rolling, and double-sided coating, the surface density was 126 g / m 2 , compacted density is 1.65g / cm 3 After cutting, a 52mm×72mm negative electrode sheet is obtained. The N / P ratio of the positive and negative electrodes is 1.1.

[0103] Preparation of battery: The battery was made in a dry room with an ambient dew point of ≤-35°C, the separator was folded in a Z shape, the positive electrode sheet and the negative electrode sheet were placed on each side, the positive electrode sheet had 18 layers, the negative electrode sheet had 19 layers, the positive electrode, the separator, and the negative electrode were aligned and stacked in order, the alumina-surface separator was coated on the positive electrode to obtain an electrode group, and then the electrode group was fixed with polyimide tape and then the ear was welded, and then placed in an aluminum-plastic film, and then vacuum-baked at 90°C for 12h, and the above-prepared electrolyte 1 was injected after cooling, and finally vacuum packaged, high-temperature soaked at 45°C, hot pressed at 45°C (pressure coefficient 6kg / cm 2 ), 45°C high temperature aging, secondary sealing, and capacity division, an experimental battery 1 with a capacity of about 2.5Ah was obtained. The formation conditions are: charging to 4.0V at 0.02C, standing for 5 minutes, then charging to 4.8V at 0.05C, aging at 45°C for 24 hours, secondary sealing of the battery, and capacity division at a rate of 0.1C.

[0104] Example 2

[0105] The specific steps for preparing compound (II) are as follows:

[0106]

[0107] Under nitrogen atmosphere, 100 mL of ultra-dry N,N-dimethylformamide (DMF) was added to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, followed by N-propynylpyrrolidine (10.91 g, 100.00 mmol) and chloromethyltrimethylsilane (13.42 g, 110 mmol), followed by stirring and heating, and the mixture was reacted at 80°C for 24 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and then washed with 100 mL of anhydrous ether, and the solvent was removed by concentration under reduced pressure to obtain intermediate 2 with a yield of 80.7%. Subsequently, intermediate 2 (11.56 g, 50.00 mmol), lithium difluorodicyanoethoxyborate (9.80 g, 50.00 mmol) and 100 mL of deionized water were added to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, and the reaction was stopped after stirring for 3 h. After the solvent was removed by distillation under reduced pressure, the product was washed three times with 50 mL of dichloromethane and finally concentrated and dried to obtain the target ionic liquid compound (II) with a yield of 75.3%. HRMS (m / z): calcd.for C 17 H 30 O2N3F2BSi:385.22, found 385.14.

[0108] Electrolyte 2 and experimental battery 2 were prepared according to the method of Example 1, except that the functional ionic liquid additive added to electrolyte 2 was compound (II), wherein the usage amounts of LiPF6, LiDODFP, organic solvent, PS, DTD and ionic liquid compound (II) were 10%, 5%, 80%, 2%, 1% and 2% of the total mass of the electrolyte, respectively.

[0109] Example 3

[0110] The specific steps for preparing compound (III) are as follows:

[0111]

[0112] Under nitrogen atmosphere, 100 mL of ultra-dry N,N-dimethylformamide (DMF) was added to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, followed by 1-methyl-3-vinylpyrrolidine (11.11 g, 100.00 mmol) and chloromethyltrimethylsilane (13.42 g, 110 mmol), followed by stirring and heating, and the mixture was reacted at 80 °C for 24 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and then washed with 100 mL of anhydrous ether, and the solvent was removed by concentration under reduced pressure to obtain intermediate 3 with a yield of 83.8%. Subsequently, intermediate 2 (11.66 g, 50.00 mmol), lithium difluorodicyanoethoxyborate (9.80 g, 50.00 mmol) and 100 mL of deionized water were added to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, and the reaction was stopped after stirring for 3 h. After the solvent was removed by distillation under reduced pressure, the product was washed three times with 50 mL of dichloromethane and finally concentrated and dried to obtain the target ionic liquid compound (III) with a yield of 77.1%. HRMS (m / z): calcd.for C 17 H 32 O2N3F2BSi:387.23,found387.29.

[0113] Electrolyte 3 and experimental battery 3 were prepared according to the method of Example 1, except that the solvent in electrolyte 3 was propylene carbonate (PC), fluoroethylene carbonate (FEC), di(2,2,2-trifluoroethyl) carbonate (TFEC), ethyl methyl carbonate (EMC) and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (HFE), and the mass ratio was 5:10:10:40:35, and the functional ionic liquid additive added was compound (III), wherein the usage amounts of LiPF6, LiDODFP, organic solvent, PS, DTD and ionic liquid compound (III) were 10%, 6%, 80%, 1%, 1% and 2% of the total mass of the electrolyte, respectively.

[0114] Example 4

[0115] The specific steps for preparing compound (IV) are as follows:

[0116]

[0117] Under nitrogen atmosphere, 100 mL of ultra-dry N,N-dimethylformamide (DMF) was added to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, followed by 3-ethynyl-1-methylpyrrolidine (10.91 g, 100.00 mmol) and chloromethyltrimethylsilane (13.42 g, 110 mmol), followed by stirring and heating, and the mixture was reacted at 80°C for 24 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and then washed with 100 mL of anhydrous ether, and the solvent was removed by concentration under reduced pressure to obtain intermediate 4 with a yield of 81.9%. Subsequently, intermediate 4 (11.56 g, 50.00 mmol), lithium difluorodicyanoethoxyborate (9.80 g, 50.00 mmol) and 100 mL of deionized water were added to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, and the reaction was stopped after stirring for 3 h. After the solvent was removed by distillation under reduced pressure, the product was washed three times with 50 mL of dichloromethane and finally concentrated and dried to obtain the target ionic liquid compound (IV) with a yield of 76.9%. HRMS (m / z): calcd.for C 17 H 30 O2N3F2BSi:385.22,found385.31.

[0118] Electrolyte 4 and experimental battery 4 were prepared according to the method of Example 1, except that the lithium salts added to electrolyte 4 were LiPF6 and lithium tetrafluoroborate (LiBF4), and the additives were PS, tris(trimethylsilyl) phosphate (TMSP) and ionic liquid compound (IV), wherein the amounts of LiPF6, LiBF4, organic solvent, PS, TMSP and ionic liquid compound (IV) used were 10%, 4%, 80.7%, 3%, 0.3% and 2% of the total mass of the electrolyte, respectively.

[0119] Example 5

[0120] The specific steps for preparing compound (V) are as follows:

[0121]

[0122] Under nitrogen atmosphere, 100 mL of ultra-dry N,N-dimethylformamide (DMF) was added to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, followed by 1-methyl-2,5-dicyanopyrrolidine (13.52 g, 100.00 mmol) and chloromethyltrimethylsilane (13.42 g, 110 mmol), followed by stirring and heating, and the mixture was reacted at 80°C for 24 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and then washed with 100 mL of anhydrous ether, and the solvent was removed by concentration under reduced pressure to obtain intermediate 5 with a yield of 76.2%. Subsequently, intermediate 5 (12.86 g, 50.00 mmol), lithium difluorodicyanoethoxyborate (9.80 g, 50.00 mmol) and 100 mL of deionized water were added to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, and the reaction was stopped after stirring for 3 h. After the solvent was removed by distillation under reduced pressure, the product was washed three times with 50 mL of dichloromethane and finally concentrated and dried to obtain the target ionic liquid compound (V) with a yield of 75.7%. HRMS (m / z): calcd.for C 17 H 28 O2N5F2BSi:411.21,found411.35.

[0123] Electrolyte 5 and experimental battery 5 were prepared according to the method of Example 1, except that the lithium salts added to electrolyte 5 were LiPF6 and lithium difluorooxalatoborate (LiODFB), and the additives were PS, DTD, hexamethylene diisocyanate (HDMI) and ionic liquid compound (V), wherein the usage amounts of LiPF6, LiODFB, organic solvent, PS, DTD, HDMI and ionic liquid compound (V) were 10%, 5%, 79.5%, 2%, 1%, 0.5% and 2% of the total mass of the electrolyte, respectively.

[0124] Example 6

[0125] The specific steps for preparing compound (VI) are as follows:

[0126]

[0127] Under nitrogen atmosphere, 100 mL of ultra-dry N,N-dimethylformamide (DMF) was added to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, followed by 1-methyl-3,4-difluoropyrrolidine (12.11 g, 100.00 mmol) and chloromethyltrimethylsilane (13.42 g, 110 mmol), followed by stirring and heating, and the mixture was reacted at 80°C for 24 h. After the reaction was completed, the solvent was removed by distillation under reduced pressure, and then washed with 100 mL of anhydrous ether, and the solvent was removed by concentration under reduced pressure to obtain intermediate 6 with a yield of 75.9%. Subsequently, intermediate 6 (12.16 g, 50.00 mmol), lithium difluorodicyanoethoxyborate (9.80 g, 50.00 mmol) and 100 mL of deionized water were added to a clean and dry 250 mL three-necked flask equipped with a magnetic rotor, and the reaction was stopped after stirring for 3 h. After the solvent was removed by distillation under reduced pressure, the product was washed three times with 50 mL of dichloromethane and finally concentrated and dried to obtain the target ionic liquid compound (VI) with a yield of 74.4%. HRMS (m / z): calcd.for C 15 H 28 O2N3F4BSi:397.20,found397.32.

[0128] Electrolyte 6 and experimental battery 6 were prepared according to the method of Example 1, except that the lithium salts added to electrolyte 6 were LiPF6, lithium bis(fluorosulfonyl)imide (LiFSI) and lithium bis(oxalatoborate) (LiBOB), and the additives were PS, DTD, lithium difluorophosphate (LiPO2F2) and ionic liquid compound (VI), wherein the usage amounts of LiPF6, LiFSI, LiBOB, organic solvent, PS, DTD, LiPO2F2 and ionic liquid compound (VI) were 10%, 3%, 2%, 79.2%, 2%, 1%, 0.8% and 2% of the total mass of the electrolyte, respectively.

[0129] Example 7

[0130] Electrolyte 7 and experimental battery 7 were prepared according to the method of Example 1, except that the additives added to electrolyte 7 were PS, succinonitrile (ADN) and ionic liquid compound (VI), wherein the usage amounts of LiPF6, LiDODFP, organic solvent, PS, ADN and ionic liquid compound (VI) were 10%, 5%, 81.5%, 2%, 1% and 0.5% of the total mass of the electrolyte, respectively.

[0131] Example 8

[0132] Electrolyte 8 and experimental battery 8 were prepared according to the method of Example 1, except that the functional ionic liquid additive added to electrolyte 8 was compound (VI), wherein the usage amounts of LiPF6, LiDODFP, organic solvent, PS, DTD and ionic liquid compound (VI) were 10%, 5%, 79%, 2%, 1% and 3% of the total mass of the electrolyte, respectively.

[0133] Comparative Example 1

[0134] The electrolyte 9 and the experimental battery 9 were prepared according to the method of Example 1, except that the usage amounts of LiPF6, LiDODFP, organic solvent, PS and DTD were 10%, 5%, 82%, 2% and 1% of the total mass of the electrolyte respectively.

[0135] Comparative Example 2

[0136] The electrolyte 10 and the experimental battery 10 were prepared according to the method of Example 1, except that the additives added to the electrolyte 10 were PS, DTD and N-methyl-N-butyl-piperidinium-bistrifluoromethylsulfonamide (PP14TFSI), wherein the usage amounts of LiPF6, LiDODFP, organic solvent, PS, DTD and PP14TFSI were 10%, 5%, 80%, 2%, 1% and 2% of the total mass of the electrolyte, respectively.

[0137] Comparative Example 3

[0138] The electrolyte 11 and the experimental battery 11 are prepared according to the method of Example 1, except that the additives added to the electrolyte 11 are PS, DTD and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIMTFSI), wherein the usage amounts of LiPF6, LiDODFP, organic solvent, PS, DTD and EMIMTFSI are 10%, 5%, 80%, 2%, 1% and 2% of the total mass of the electrolyte, respectively.

[0139] The electrolyte compositions and contents of Examples 1 to 8 and Comparative Examples 1 to 3 are shown in Table 1.

[0140] The lithium ion batteries prepared in Examples 1 to 8 and Comparative Examples 1 to 3 were subjected to normal temperature cycle performance test, high temperature cycle test, and low temperature discharge performance test, respectively. The results are shown in Table 1, where the test conditions are as follows:

[0141] Battery room temperature cycle test

[0142] The prepared lithium-ion battery was placed in a constant temperature room with an ambient temperature of 25°C, with a current of 0.5C and a voltage of 4.8V, and constant current and constant voltage charging to a cut-off current of 0.05C, and then discharged at a constant current of 0.5C to a voltage of 3V. The cycle was repeated 500 times, and the capacity retention rate was recorded. The nth cycle capacity retention rate (%) = (nth cycle discharge specific capacity / first cycle discharge specific capacity) × 100%.

[0143] Battery high temperature cycle test

[0144] Before the test, use an internal resistance tester to measure the internal resistance of the battery, and use the water displacement method to measure the battery volume. Then, place the prepared lithium-ion battery in a high and low temperature box at a temperature of 45°C for 2 hours to stabilize the temperature inside and outside the battery. Charge at a current of 0.5C, a voltage of 4.8V, and a constant current and constant voltage until the cut-off current is 0.05C, then discharge at a constant current of 0.5C to a voltage of 3V, cycle 500 times, and record the capacity retention rate. The capacity retention rate of the nth cycle (%) = (nth cycle discharge specific capacity / first cycle discharge specific capacity) × 100%. After the test, use the internal resistance tester to measure the internal resistance of the battery again, and use the water displacement method to measure the battery volume.

[0145] DC resistance (DCR) test

[0146] The prepared battery was fully charged after 500 cycles, and then discharged at a constant current of 1C for 30 minutes, and the SOC was adjusted to 50%. After being left for 2 hours, the voltage value V0 was recorded, and then the battery was discharged at a constant current of 3C (the actual value is recorded as I0) for 10 seconds, and the voltage value V1, DCR was recorded. (3C,10s) =(V0-V1) / I0.

[0147] Table 1. Electrolyte compositions and corresponding battery performances of various embodiments and comparative examples

[0148]

[0149]

[0150]

[0151] From the performance test results of lithium ion batteries prepared using the electrolytes prepared in Examples 1 to 8 and Comparative Examples 1 to 3 in Table 1, it can be seen that the functional ionic liquid provided by the present invention has a larger anion and cation radius than the traditional ionic liquid, which changes the solvation structure of the electrolyte, and more anions participate in forming a highly stable SEI film, thereby improving the high-pressure and high-temperature tolerance of the positive and negative electrode interfaces, and greatly improving the high-voltage cycle performance of the battery.

[0152] This is because compared with Comparative Examples 2 and 3, the functional ionic liquids provided by the present invention in Examples 1 to 6 have relatively small anion and cation molecular structures, weak intermolecular forces, and low viscosity. In addition, trimethylsilane is introduced into the pyrrole cation to increase the polarity of the ionic liquid, reduce the intermolecular forces, further reduce the viscosity of the ionic liquid, and optimize the SEI film composition, reduce impedance, and improve the low-temperature discharge performance of the battery.

[0153] Moreover, compared with Comparative Examples 2 and 3, the special functional groups contained in the anion and cation structures of Examples 1 to 8, trimethylsilyl and cyano, can also play the role of removing free acids in the electrolyte, complexing and stabilizing high-valent transition metals, etc., reducing continuous side reactions during high-voltage cycles, and reducing battery DCIR, thereby further improving the high-temperature electrochemical performance of high-voltage lithium-ion batteries.

[0154] Compared with Examples 6, 7, and 8, the optimal addition amount of the functional ionic liquid is 2%. If the addition amount is too small, the performance improvement will be small. If the addition amount is too large, the membrane impedance will increase, the battery DCIR will increase, and the cycle performance will deteriorate.

[0155] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A functional ionic liquid additive, characterized in that: It has the structure shown in formula B: Wherein, m and n are each independently an integer of 1 to 5; R1 is selected from hydrogen, C1-C5 alkyl, C2-C5 alkenyl or C2-C5 alkynyl; R2 to R5 are each independently selected from hydrogen, C1 to C5 alkyl, C2 to C5 alkenyl, C2 to C5 alkynyl, halogen atom or C1 to C5 nitrile; R6 is selected from C1-C5 alkyl groups.

2. The functional ionic liquid additive according to claim 1, characterized in that: It has the structure shown in structural formula A: wherein R1 is selected from hydrogen, C1-C5 alkyl, C2-C5 alkenyl or C2-C5 alkynyl; R2 to R5 are each independently selected from hydrogen, a C1 to C5 alkyl group, a C2 to C5 alkenyl group, a C2 to C5 alkynyl group, a halogen atom or a C1 to C5 nitrile group.

3. The functional ionic liquid additive according to claim 2, characterized in that: Said R1 is selected from hydrogen, methyl, ethyl, vinyl, ethynyl or propynyl; R2 to R5 are each independently selected from hydrogen, vinyl, acetylene, fluorine or acetonitrile.

4. The functional ionic liquid additive according to claim 1, characterized in that: The functional ionic liquid additive has at least one of the structures shown in formula (I) to formula (VI):

5. A method for preparing a functional ionic liquid additive, characterized in that: The following steps are involved: The lithium borate salt represented by formula (VII) is reacted with the compound represented by formula (VIII) to obtain a functional ionic liquid additive having a structure represented by formula B; Wherein, m and n are each independently an integer of 1 to 5; R1 is selected from hydrogen, C1-C5 alkyl, C2-C5 alkenyl or C2-C5 alkynyl; R2 to R5 are each independently selected from hydrogen, C1 to C5 alkyl, C2 to C5 alkenyl, C2 to C5 alkynyl, halogen atom or C1 to C5 nitrile; R6 is selected from C1-C5 alkyl groups.

6. A non-aqueous electrolyte, characterized in that The invention comprises the functional ionic liquid additive according to any one of claims 1 to 4 or the functional ionic liquid additive prepared by the preparation method according to claim 5.

7. The non-aqueous electrolyte according to claim 6, characterized in that The mass of the functional ionic liquid additive is 0.5% to 3% of the mass of the non-aqueous electrolyte.

8. The non-aqueous electrolyte according to claim 6, characterized in that The non-aqueous electrolyte also includes a lithium salt, a non-aqueous solvent and an auxiliary electrolyte additive; The mass of the lithium salt is 14% to 16% of the mass of the non-aqueous electrolyte; The mass of the non-aqueous solvent is 79% to 81.5% of the mass of the non-aqueous electrolyte; The mass of the auxiliary electrolyte additive is 2% to 3.8% of the mass of the non-aqueous electrolyte.

9. The non-aqueous electrolyte according to claim 8, characterized in that The lithium salt is selected from one or more of lithium hexafluorophosphate, lithium perchlorate, lithium tetrafluoroborate, lithium bis(trifluoromethylsulfonyl imide), lithium bis(fluorosulfonyl imide), lithium bis(oxalatoborate), lithium difluorooxalatoborate and lithium difluorobis(oxalatophosphate); The non-aqueous solvent is selected from organic esters and / or ether solvents; the organic ester is selected from one or more of ethylene carbonate, propylene carbonate, butylene carbonate, dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, ethyl formate, ethyl acetate, propyl acetate, propyl propionate, methyl trifluoroethyl carbonate, fluoroethylene carbonate and di(2,2,2-trifluoroethyl) carbonate; the ether solvent is selected from one or more of dimethyl ether, diethyl ether, methyl ethyl ether, ethylene glycol dimethyl ether, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether and 1H,1H,5H-octafluoropentyl-1,1,2,2-tetrafluoroethyl ether; The auxiliary electrolyte additive is selected from one or more of unsaturated cyclic carbonate compounds, fluorinated carbonate compounds, sulfate compounds, sulfonate compounds, sulfonimide compounds, phosphate compounds, silane compounds, trimethylsilyl ester compounds, isocyanate compounds, nitrile compounds and lithium salt additives.

10. A high voltage lithium ion battery, characterized in that: The non-aqueous electrolyte comprises the non-aqueous electrolyte according to any one of claims 6 to 9.

Citation Information

Patent Citations

  • Performance additives for improving the wetting properties of ionic liquids on solid surfaces

    CN101502770A

  • Functionalized ionic liquid electrolyte for lithium secondary battery

    CN103035945A

  • Alkyl silicyl lithium battery polymer electrolyte resistant to high voltage, preparation method and application thereof in all-solid-state lithium battery

    CN108242563A

  • Silicon-cyanogen electrolyte additive for high-voltage lithium ion battery, electrolyte and battery

    CN111416153A

  • Electrolyte silicon-based pyridine additive for high-voltage lithium ion battery, electrolyte and battery

    CN111416154A